An analysis of the legal regime governing transfer of cases from the International Criminal Tribunal for Rwanda (ICTR) to the Rwandan domestic justice system - Ingabire, Mackline (2010)
The International Criminal Tribunal for Rwanda (ICTR), established by the United Nations Security Council was originally set to wind up its affairs in 2010. However, by Resolution 1901 of the Security Council, ICTR's mandate has been extended to 2012.This will necessitate the transfer of residual cases to national courts for trial after it has closed. Rwanda considers itself a suitable candidate for referral, and hence has supported the ICTR Prosecutor's requests (five requests) for referral to its national courts